Spectral extension and synchronization of microcombs in a single microresonator - Shuangyou Zhang (Nature Portfolio, 2020)
Broadband frequency combs are a key enabling technology for frequency metrology and spectroscopy. Here, the authors demonstrate that the spectrum of a soliton microcomb can be extended by bichromatic pumping resulting in two combs that synchronize their repetition rate via cross-phase modulation.